Thin wall injection-overmoulding of polyamide 6/polypropylene multilayer parts: influence of processing conditions on thermomechanical properties of the layer assembly. (2016) - Macedo, Sandra; Lafranche, Eric; Martins, Carla I.; Douchain, Catherine; Loux, Cyril; Krawczak, Patricia
Plastic packaging has many development drivers: providing enhanced functionalities, better barrier properties, and longer shelf life while taking into account the environment and respecting criteria of thermo-mechanical performance. As a single polymer cannot satisfy all these requirements, plastic products are often made of more than one polymer and/or more than one single layer, each one having different but complementary properties. This work aims at investigating the over-moulding of PA6 over PP-g-MA in order to optimise the adhesion of multilayer PP/PA6 injection-moulded parts, as PP and PA6 are not miscible. Among the processing parameters, the holding pressure was found to be the main parameter governing the peeling strength of the multilayer assembly. The change of the polymer structure was evaluated by optical microscopy coupled to infrared spectroscopy and scanning electron microcopy. The PA6/PP-g-MA interfacial properties were investigated by dynamic rheology and assessed in term of quadratic distance of diffusion through the interface. For this purpose, the variation of the temperature field of the assembly during the cooling stage of the manufacturing process was simulated using the heat transfer module of a finite elements software package.